A systematic review and meta-analysis on the effect of selective serotonin reuptake inhibitors on endothelial function. (3rd October 2022) - Delialis, D; Mavraganis, G; Dimoula, A; Ajdini, E; Bampatsias, D; Dimopoulou, A M; Sianis, A; Maneta, E; Neofytou, O; Petropoulos, I; Konstantinou, G; Misegiannidis, A; et al.
Abstract: Background: Depression and atherosclerotic cardiovascular disease (ASCVD) are commonly clustered in affected patients. Endothelial dysfunction is an early marker of ASCVD while also reported in patients with depression. Emerging evidence suggests that selective serotonin receptor inhibitors (SSRIs) may improve endothelial function. However, clinical studies assessing flow-mediated dilation (FMD), the gold-standard method to evaluate conduit artery endothelial function, in response to SSRIs treatment included limited number of patients and did not provide consistent results. Purpose: In the present study we aim to evaluate the effect of SSRIs treatment on endothelial function assessed by longitudinal changes in FMD. Methods: We performed a systematic review to retrieve and subsequently meta-analyze eligible studies in patients with depression who received SSRIs and had available measurements of FMD change before and after treatment. Results: In 5 studies and 323 individuals in total, SSRIs were associated with increased FMD at the end of follow-up compared to baseline measurement (pooled mean change 1.97%, 95% CI 0.17, 3.77, P=0.032, I 2 =87.4%). These results did not substantially change when analysis was restricted to patients with history of atherosclerotic cardiovascular disease (ASCVD). Similarly, FMD changes were higher in individuals receiving SSRIs compared to not-treated subjects (pooled mean difference 2.5%. 95% CI 0.7, 4.2, P<0.001, I 2 =82.7%). Substantial heterogeneity regarding with respect to follow-up duration, demographics, and SSRIs agents. Conclusion: SSRIs significantly improve FMD, the gold-standard marker of endothelial function. Further investigation is warranted for the role of FMD as a possible therapeutic biomarker in patients with depression and established or subclinical ASCVD. Prospero registration: CRD42021252241 Funding Acknowledgement: Type of funding sources: None.